Children with cerebral palsy: Family and parent demographic characteristics and family strengths in Greece and Italy. (October 2021) - Tsibidaki, Assimina
The study focuses on families raising a child with cerebral palsy to investigate family strengths and their association with family and parent demographic characteristics in Greece and Italy. Participants were 120 parents raising a biological child with cerebral palsy. Data collection used a self-report questionnaire and the Family Strengths Inventory. According to the findings, families share a high sense of family strengths, which is mainly represented in the high sense of 'pride' and 'accord'. In addition, demographic characteristics seem to be important predictors of well-being and strengthen parents and families raising a child with cerebral palsy.